2023
DOI: 10.1038/s41467-023-37252-y
|View full text |Cite
|
Sign up to set email alerts
|

The m6A reader PRRC2A is essential for meiosis I completion during spermatogenesis

Abstract: N6-methyladenosine (m6A) and its reader proteins YTHDC1, YTHDC2, and YTHDF2 have been shown to exert essential functions during spermatogenesis. However, much remains unknown about m6A regulation mechanisms and the functions of specific readers during the meiotic cell cycle. Here, we show that the m6A reader Proline rich coiled-coil 2A (PRRC2A) is essential for male fertility. Germ cell-specific knockout of Prrc2a causes XY asynapsis and impaired meiotic sex chromosome inactivation in late-prophase spermatocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 95 publications
0
4
0
Order By: Relevance
“…In contrast to HIV-1, HIV-2 downregulated NCAPH and PRRC2A, two proteins that are known to play an important role in cell proliferation and migration [ 77 , 78 ]. Retroviruses and, indeed, DNA and RNA viruses, in general, are known to modulate the cell cycle and cellular proliferation in order to facilitate viral replication and survival [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to HIV-1, HIV-2 downregulated NCAPH and PRRC2A, two proteins that are known to play an important role in cell proliferation and migration [ 77 , 78 ]. Retroviruses and, indeed, DNA and RNA viruses, in general, are known to modulate the cell cycle and cellular proliferation in order to facilitate viral replication and survival [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…PRRC2A stabilises Olig2 mRNAs by binding to the m 6 A within the coding sequence region of Olig2 and this stabilisation effect is reversible through the action of the m 6 A demethylase FTO. However, another recent study showed that PRRC2A recognises spermatogonia-specific transcripts and down-regulate their RNA abundance [ 68 ], thereby maintaining the spermatocyte expression pattern during the meiosis prophase. It is important to note that this analysis was conducted on a transcriptome-wide scale rather than focusing on individual transcripts.…”
Section: Rna Stability Regulated By Other Non-canonical M 6...mentioning
confidence: 99%
“… 56 Expectedly, more m 6 A-binding proteins are identified to expand the reservoir of m 6 A readers for executing different post-transcriptional regulation of RNAs, such as heterogeneous nuclear ribonucleoprotein (HNRNP) family, 57 fragile X mental-retardation protein (FMR1), 58 , 59 and proline-rich coiled-coil 2A. 60 , 61 …”
Section: A Readersmentioning
confidence: 99%